A Defense Mechanism for Distributed Denial of Service Attack in Software-Defined Networks - Shibo Luo; Jun Wu; Jianhua Li; Bei Pei (International Conference on Frontier of Computer Science and Technology (Print), 2015)
Distributed Denial of Service (DDoS) attack is a major threat to Internet based killer applications, such as independent news web sites, e-business and online games. Detecting and blocking such clever attacks has become difficult. Software-Defined Networks (SDN) has emerged as a future communication network architecture which decouples network control and forwarding. It has some particular features such as central control and programmability to combat against DDoS attack. In this paper, we survey DDoS attacks and existing defense mechanisms, and draw a conclusion of the needs of defense mechanism for successful combating against DDoS. Then, we analyze the particular features of SDN and conclude it is conducive to countermeasure DDoS attack. According the analysis, we construct a defense mechanism for DDoS in SDN. At last, we illustrate how this mechanism could combat against DDoS attacks through a working example.